Amplifier predistortion adaptation system - Simões, Samuel Martins (2021)
In today’s world, with the demands needed to fulfil the challenges on 5G, it is important that Radio Frequency (RF) amplifiers work in a more efficient way. To meet this objective, one of the existing options focuses on the usage of linearization techniques to improve amplifier performance on its saturation zone. One relevant technique, which has great efficiency and linearization potential is the application of predistorters. They can be used with a pre-programed configuration or they may adapt their response in real-time, with the help of signal readings at the power amplifier’s (PA) output. This work focuses on the design and implementation of an amplifier predistortion real-time adaption system. This system measures the spectral power of an RF signal with the purpose of, in the future, incorporating a predistorter automatic adaption system. Having the Multiple-Input and Multiple-Output (MIMO) transmitter scenario as background, where a single transmitter is built from several low-power and wideband amplifiers (each of which require linearization actions), the developed spectrum measurement system assumed, from the start, the requirements of achieving a very low cost and reduced space confinement.